Poly[[μ(2)-aqua-tetraaquadi-μ(3)-malonato-nickel(II)strontium(II)] dihydrate] - Guo, Ming-Lin (International Union of Crystallography, 2010)
The unit-cell parameters for the title mixed-metal coordination polymer, {[NiSr(C(3)H(2)O(4))(2)(H(2)O)(5)]·2H(2)O}(n), which is isostructural with its Co-containing analogue, were reported previously [Gil de Muro et al. (1999 ▶). Eur. J. Inorg. Chem. pp. 935–943]; the full crystal structure including a description of the hydrogen bonding is reported here. The Sr(2+) ion is bonded to five O atoms from three different malonate dianions and four water molecules, displaying a distorted tricapped trigonal–prismatic coordination geometry. Two malonate dianions, two water molecules and one Ni(2+) ion build up a dianionic [Ni(C(3)H(2)O(4))(2)(H(2)O)(2)](2−) unit incorporating a slightly distorted NiO(6) octahedron, which coordinates to three nearby Sr(2+) ions. This arrangement creates a metal-organic framework having a 20-membered ring with four Ni and six Sr atoms lying in the bc plane. The coordinated and uncoordinated water molecules are responsible for the formation of two D5 hydrogen-bonded water chains within the 20-membered ring and they are linked into an R4 water cluster via two bifurcated O—H⋯(O,O) links.